Methylome analysis of ALS patients and presymptomatic mutation carriers in blood cells - Ruf, Wolfgang P.; Hannon, Eilis; Freischmidt, Axel; Grozdanov, Veselin; Brenner, David; Müller, Kathrin; Knehr, Antje; Günther, Kornelia; Dorst, Johannes; Ammerpohl, Ole; Danzer, Karin M.; Mill, Jonathan; et al. (Neurobiology of aging, 2022)
Amyotrophic lateral sclerosis (ALS) is a fatal motoneuron disease with a monogenic cause in approximately 10% of cases. However, familial clustering of disease without inheritance in a Mendelian manner and the broad range of phenotypes suggest the presence of epigenetic mechanisms. Hence, we performed an epigenome-wide association study on sporadic, symptomatic and presymptomatic familial ALS cases with mutations in C9ORF72 and FUS and healthy controls studying DNA methylation in blood cells. We found differentially methylated DNA positions (DMPs) and regions embedding DMPs associated with either disease status, C9ORF72 or FUS mutation status. One DMP reached methylome-wide significance and is attributed to a region encoding a long non-coding RNA (LOC389247). Furthermore, we could demonstrate co-localization of DMPs with an ALS-associated GWAS region near the SCN7A/SCN9A and XIRP2 genes. Finally, a classifier model that predicts disease status (ALS, healthy) classified all but one presymptomatic mutation carrier as healthy, suggesting that the presence of ALS symptoms rather than the presence of ALS-associated genetic mutations is associated with blood cell DNA methylation.
Online verfügbar: 20 April 2022, Artikelversion: 7 May 2022
Gesehen am 31.10.2023